The Role of Education and Public Awareness in Preventing Reproductive System Cancer - Monalisa, Monalisa; Kusumawaty, Ira; Yunike, Yunike; Sri Ananingsih, Esti; Elfrida, Solha; Podojoyo, Podojoyo; Inastyarikusuma, Tarrinni (International Journal Scientific and Professional, 2024)
Cancers of the reproductive system, including cervical, ovarian, and prostate cancer, are one of the leading causes of morbidity and mortality worldwide. In Indonesia, the incidence of reproductive system cancer is still high, mainly due to low early detection and a lack of public awareness about prevention. This study aims to evaluate the role of education and increasing public awareness in preventing cancer of the reproductive system. This research method uses a quantitative approach with a cross-sectional study design. Data was collected through a survey involving 150 respondents from various backgrounds in three large cities. The research results show that the level of public knowledge about reproductive system cancer is still low. Only 45% of respondents knew the risk factors and early symptoms of reproductive system cancer and only 30% had undergone routine examinations. Health education delivered through various media, including health campaigns, seminars and social media, has effectively increased public awareness and knowledge. Respondents who had participated in health education programs showed significant increases in knowledge and preventive behaviour, such as having regular check-ups and adopting a healthy lifestyle. Research finds that the main obstacles in preventing cancer of the reproductive system are lack of access to health services and low levels of public education, so more inclusive and accessible strategies are needed to disseminate health information. Educational programs involving local communities and community leaders can help overcome these barriers. The research concludes that education and increasing public awareness play a crucial role in preventing cancer of the reproductive system. Implementation of effective education programs can reduce the incidence of cancer through early detection and changes to healthier behaviour. The government and health organizations need to work together to develop and expand health education programs that can be accessed by all levels of society, especially in areas that have low levels of knowledge about cancer of the reproductive system.